Gene Expression Profiles during In Vivo Human Rhinovirus Infection: Insights into the Host Response - Proud, David; Turner, Ronald B; Winther, Birgit; Wiehler, Shahina; Tiesman, Jay P; Reichling, Tim D; Juhlin, Kenton D; Fulmer, Andy W; Ho, Begonia Y; Walanski, Amy A; Poore, Cathy L; Mizoguchi, Haruko; et al. (American journal of respiratory and critical care medicine, 2008)
Human rhinovirus infections cause colds and trigger exacerbations of lower airway diseases. To define changes in gene expression profiles during in vivo rhinovirus infections. Nasal epithelial scrapings were obtained before and during experimental rhinovirus infection, and gene expression was evaluated by microarray. Naturally acquired rhinovirus infections, cultured human epithelial cells, and short interfering RNA knockdown were used to further evaluate the role of viperin in rhinovirus infections. Symptom scores and viral titers were measured in subjects inoculated with rhinovirus or sham control, and changes in gene expression were assessed 8 and 48 hours after inoculation. Real-time reverse transcription-polymerase chain reaction for viperin and rhinoviruses was used in naturally acquired infections, and viperin mRNA levels and viral titers were measured in cultured cells. Rhinovirus-induced changes in gene expression were not observed 8 hours after viral infection, but 11,887 gene transcripts were significantly altered in scrapings obtained 2 days postinoculation. Major groups of up-regulated genes included chemokines, signaling molecules, interferon-responsive genes, and antivirals. Viperin expression was further examined and also was increased in naturally acquired rhinovirus infections, as well as in cultured human epithelial cells infected with intact, but not replication-deficient, rhinovirus. Knockdown of viperin with short interfering RNA increased rhinovirus replication in infected epithelial cells. Rhinovirus infection significantly alters the expression of many genes associated with the immune response, including chemokines and antivirals. The data obtained provide insights into the host response to rhinovirus infection and identify potential novel targets for further evaluation.